Memory and disgust: Effects of appearance-congruent and appearance-incongruent information on source memory for food. Issue 5 (27th May 2016) - Mieth, Laura; Bell, Raoul; Buchner, Axel
Abstract : The present study was stimulated by previous findings showing that people preferentially remember person descriptions that violate appearance-based first impressions. Given that until now all studies used faces as stimuli, these findings can be explained by referring to a content-specific module for social information processing that facilitates social orientation within groups via stereotyping and counter-stereotyping. The present study tests whether the same results can be obtained with fitness-relevant stimuli from another domain—pictures of disgusting-looking or tasty-looking food, paired with tasty and disgusting descriptions. A multinomial model was used to disentangle item memory, guessing and source memory. There was an old–new recognition advantage for disgusting-looking food. People had a strong tendency towards guessing that disgusting-looking food had been previously associated with a disgusting description. Source memory was enhanced for descriptions that disconfirmed these negative, appearance-based impressions. These findings parallel the results from the social domain. Heuristic processing of stimuli based on visual appearance may be complemented by intensified processing of incongruent information that invalidates these first impressions.